2015
DOI: 10.1002/jcsm.12037
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia-associated adipose tissue morphological rearrangement in gastrointestinal cancer patients

Abstract: Background and aimsCachexia is a syndrome characterized by marked involuntary loss of body weight. Recently, adipose tissue (AT) wasting has been shown to occur before the appearance of other classical cachexia markers. We investigated the composition and rearrangement of the extracellular matrix, adipocyte morphology and inflammation in the subcutaneous AT (scAT) pad of gastrointestinal cancer patients.MethodsSurgical biopsies for scAT were obtained from gastrointestinal cancer patients, who were signed up in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
107
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 50 publications
(115 reference statements)
12
107
0
2
Order By: Relevance
“…Many of these cytokines have been implicated in the development and progression of tumours . Our research group has previously demonstrated a relationship between changes in cytokines and the growth factor profile and wasting in CC patients . Circulating levels of pro‐inflammatory adipokines have been shown to correlate with the total mass of visceral adipose tissue .…”
Section: Introductionmentioning
confidence: 97%
“…Many of these cytokines have been implicated in the development and progression of tumours . Our research group has previously demonstrated a relationship between changes in cytokines and the growth factor profile and wasting in CC patients . Circulating levels of pro‐inflammatory adipokines have been shown to correlate with the total mass of visceral adipose tissue .…”
Section: Introductionmentioning
confidence: 97%
“…In the last years, data from clinical studies have implicated pro‐inflammatory cytokines in the pathogenesis of CAC. In previous studies, we demonstrated that the tumour micro‐environment and the adipose tissue contribute to systemic pro‐inflammatory profile and to the alterations of immunomodulatory function in cachectic patients . Zhang et al .…”
Section: Introductionmentioning
confidence: 81%
“…Chronic inflammation has been reported in the majority of patients with CAC and causes disruption of morphofunctional aspects of many tissues, such as the brain, the adipose tissue, and the muscle, while also affecting tumour biology . The secretory profile of the tumour may be associated with cachexia–muscle wasting, as proposed by de Matos‐Neto et al .…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, while adipose tissue fibrosis in the context of obesity is well described, increased adipose ECM deposition, fibrosis, and immune cell infiltration are also observed in cancer-associated cachexia (35). Abdominal subcutaneous adipose depots of lean cachectic subjects bearing gastrointestinal cancers displayed extensive adipose ECM remodeling, including a dramatic increase in deposition of collagens I, III, and VI as well as elastin and fibronectin (11).…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 99%